Enhanced hole carrier transport due to increased intermolecular contacts in small molecule based field effect transistors - Dharmapurikar, Satej S.; Arulkashmir, Arulraj; Das, Chayanika; Muddellu, Pooja; Krishnamoorthy, Kothandam (ACS Applied Materials & Interfaces, 2013)
Small molecules and oligomers can be synthesized with very high purity and precise molecular weights, but they often do not form uniform thin films while processed from solution. Decreased intermolecular contacts between the small molecules are another disadvantage. To increase the intermolecular contacts in small molecules, we have chosen i-indigo, as one of the conjugated molecular units. The electron poor i-indigo has been connected with electron rich triphenylamine to synthesize a donor-acceptor-donor type small molecule. The propeller shaped triphenylamine helps to increase the solubility of the small molecule as well as isotropic charge transport. The intermolecular spacing between the molecules has been found to be low and did not vary as a function of thermal annealing. This implies that the intermolecular contacts between the small molecules are enhanced, and they do not vary as a function of thermal annealing. Organic field effect transistors (OFET) fabricated using a small molecule exhibited a hole carrier mobility (mu) of 0.3 cm(2)/(V s) before thermal annealing. A marginal increase in mu was observed upon thermal annealing at 150 degrees C, which has been attributed to changes in thin film morphology. The morphology of the thin films plays an important role in charge transport in addition to the intermolecular spacing that can be modulated with a judicious choice of the conjugated molecular unit.
Keywords: hole mobility; i-indigo; organic field effect transistor; quadrupole interaction; small molecules; triphenylamine

Disassembly of micelles in nanoscopic space to prepare concentric nanotubes with variable hydrophobic interiors - Das, Chayanika; Krishnamoorthy, Kothandam (Chemical Communications, 2014)
Nanotubes with variable hydrophobic interiors were prepared by disassembling anionic micelles in the inner walls of positive charge bearing conjugated polymer nanotubes.

Phenols from green tea as a dual functional coating to prepare devices for energy storage and molecular separation - Das, Chayanika; Jain, Bhanprakash; Krishnamoorthy, Kothandam (Chemical Communications, 2015)
Polyphenols from green tea were used to electrolessly deposit gold on silk cocoons (SCs) and nanoporous aluminum oxide (AAO) templates. The gold coated cocoons were used as electrodes in supercapacitors and showed a capacitance as high as 254 F g(-1) and a specific power of 2287 W kg(-1). A metal coated AAO template was used for molecular separation.

F and CF3 substituted solution processable oligo para-phenylenevinylene for ambipolar and hole-transporting organic field effect transistors - Chini, Mrinmoy Kumar; Das, Chayanika; Chatterjee, Shyambo (Chemical Physics Letters, 2016)
We have synthesized benzotrifluoromethyl group substituted para-phenylenevinylene oligomer (denoted as PI) and a cooligomer (denoted as PII) by Gilch polymerization route. The ambipolar field-effect transistor (FET) material PI shows hole and electron mobility 1 x 10 (4) cm(2) V (1) s (1) and 2 x 10 (5) cm(2) V (1) s (1) respectively. PII shows only hole mobility as high as 0.05 cm(2) V (1) s (1) as p-type material. This work highlights the progress of hole-transporting as well as ambipolar material for para-phenylenevinylene derivatives. The results are enlightened on the basis of presence of electronegative substituents and structural modification of the oligomer backbone. (C) 2016 Elsevier B.V. All rights reserved.

Flexible microsupercapacitors using silk and cotton substrates - Das, Chayanika; Krishnamoorthy, Kothandam (ACS Applied Materials & Interfaces, 2016)
Flexible microsupercapacitors (MSCs) are needed to power ultrasmall wearable electronic devices. Silk cocoons comprise microfibers of silk, which is an attractive natural resource to fabricate MSCs. These fibers are insulators; hence, they must be converted to conducting surfaces. Polyphenols from green tea have been used as a protective layer that also acted as a reducing agent for silver ions. The reduction of silver ions resulted in the formation of silver nanoparticles that subsequently reduced gold ions to gold. The gold film imparts conductivity to the silk fiber without affecting the mechanical strength of the silk fiber. The mechanical strength of uncoated silk fiber and gold coated silk fiber were found to be 5.2 and 5 GPa, respectively. A pseudocapacitive polymer, poly(3,4-ethylenedioxythiophene), was used as the active material to fabricate MSCs. The MSCs showed an impressive gravimetric capacitance of 500 F/g and areal capacitance of 62 mF/cm(2). The power and energy densities were calculated to be 2458 W/kg and 44 Wh/kg, respectively. The device was coiled on a cylinder, and the performance of the device was found to be same as that of the uncoiled device. To demonstrate that the approach is not specific to silk, we also coated gold on cotton fibers using the protocol used to coat gold on silk. Coiled and uncoiled supercapacitors were fabricated using PEDOT coated cotton fibers. The gravimetric capacitance was found to be 250 F/g with energy and power densities of 5.5 Wh/kg and 1118 W/kg, respectively. We have also demonstrated that the devices can be connected in parallel and series to improve the performance of the miniaturized devices.

Elastic compressible energy storage devices from ice templated polymer gels treated with polyphenols - Das, Chayanika; Chatterjee, Soumyajyoti; Kumaraswamy, Guruswamy; Krishnarnoorthy, Kothandam (Journal of Physical Chemistry C, 2017)
Design and fabrication of rechargeable energy storage devices that are robust to mechanical deformation is essential for wearable electronics. We report the preparation of compressible supercapacitors that retain their specific capacitance after large compression and that recover elastically after at least a hundred compression expansion cycles. Compressible supercapacitors are prepared using a facile, scalable method that readily yields centimeter-scale macroporous objects. We ice template a solution of polyethylenimine in green tea extract to prepare a macroporous cross-linked polymer gel (PG) whose walls are impregnated with green tea derived polyphenols. As the PG is insulating, we impart conductivity by deposition of gold on it. Gold deposition is done in two steps: first, silver nanoparticles are formed on the PG walls by in situ reduction by polyphenols and then gold films are deposited on these walls. Gold coated PGs (GPGs) were used as electrodes to deposit poly(3,4-ethylenedioxythiophene) as a pseudocapacitive material. The specific capacitance of PEDOT coated GPGs (PGPG) was found to be 253 F/g at 1 A/g. PGPG could be compressed and expanded over a hundred cycles without any suffering mechanical failure or loss of capacitative performance. The capacitance was found to be 243 F/g upon compressing the device to 25% of its original size (viz. compressive strain = 75%). Thus, even large compression does not affect the device performance. This device shows power and energy densities of 2715 W/kg and 22 Wh/kg, respectively, in the uncompressed state. The macroporous nature of PGPG makes it possible to fill the PGPG pores with gel electrolyte. We report that the gel electrolyte filled supercapacitor exhibited a specific capacitance of 200 F/g, which increased by 4% upon 75% compression.

Silk cocoon as counter - electrode substrate in dye - sensitized solar cells - Sudhakar, Vediappan; Das, Chayanika; Krishnamoorthy, Kothandam (ChemistrySelect, 2018)
Electrodes are vital components of energy conversion devices such as dye sensitized solar cells (DSSCs). The widely used electrodes consist of fluorine doped tin oxide (FTO) and platinum. We were interested in identifying a substrate that is available from natural resources and exhibit performance comparable to that of Pt coated FTO (Pt-FTO). Silk fibers are naturally available and they are mechanically stable. The woven silk fibers are known as silk cocoons (SCs) that structurally resemble widely used carbon paper electrodes. To impart conductivity to the insulating SCs, metal film was coated by an electroless metal plating procedure using polyphenols from green tea. The metal coated SCs were conformaly coated with a conjugated polymer and these electrodes were used as flexible electrodes in DSSCs. The flexible electrode based DSSCs exhibited a power conversion efficiency of 7.2% which is comparable to that of the DSSCs with rigid Pt-FTO based devices (7.4%).
Keywords: counter electrode; PEDOT-G-SCs; Recombination; Silk cocoons (SCs)